Understanding Smart Banking Services Adoption in Pakistan: Integrating Self-Expressiveness into UTAUT2 Model - Hassaan, Muhammad; Akhtar, Raheel; Yaseen, Asif; Imran, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
A smart banking service can be characterized as a convergence point at which technology can be adopted through mobile applications. The study examines the factors that have an impact on Pakistani bank customers' intentions to adopt smart banking services (SBS). This study used the unified theory of acceptance and use of technology (UTAUT2) as a base model and extended it by incorporating perceived self-expressiveness, which may influence individual usage of SBS. A total of 324 banking customers from five major banks in Pakistan completed a survey questionnaire in person using convenient sampling approach. The measurement and structural analysis were carried out using Smart PLS3 software. This study found that UTAUT2 significantly explained the behavioral intention (BI) to use SBS. The significant predictors of BI were facilitating conditions (FC), habits (HT), performance expectancy (PE), hedonic motivation (HM), effort expectancy (EE) and perceived self-expressiveness (SE). However, price value (PV) and social influence (SI) were not significant. FC, HT, and BI were also identified as significant factors influencing use behavior (UB). Indeed, this study has novel contribution in extending the UTAUT2 model with self-expressiveness to understand SBS adoption for the first time in Pakistan as a developing country.